2003
DOI: 10.1046/j.1469-8137.2003.00838.x
|View full text |Cite
|
Sign up to set email alerts
|

Species level patterns in 13C and 15N abundance of ectomycorrhizal and saprotrophic fungal sporocarps

Abstract: Abstract• The natural abundance of 13 C ( δ 13 C) and 15 N ( δ 15 N) of saprotrophic and ectomycorrhizal (ECM) fungi has been investigated on a number of occasions, but the significance of observed differences within and between the two trophic groups remains unclear.• Here, we examine the influence of taxonomy, site, host and time upon isotopic data from 135 fungal species collected at two forest sites in Sweden.• Mean δ 13 C and δ 15 N values differed significantly between ECM and saprotrophic fungi, with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
130
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 53 publications
21
130
2
Order By: Relevance
“…For example, I. fastigiata displayed a low nitrogen natural abundance (δ 15 N of 2.0% ), while A. strobiliformis displayed a high natural abundance (δ 15 N of 13.5% ). These results are congruent with those of several research teams (Gebauer and Dietrich, 1993, Henn and Chapela, 2001Kohzu et al, 1999;Taylor et al, 2003;Trudell et al, 2004;Zeller et al, 2007) who all observed high 15 N abundance in ectomycorrhizal fungi sporophores. The three Tuber species displayed a high δ 15 N value (9.3 to 10.4% ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For example, I. fastigiata displayed a low nitrogen natural abundance (δ 15 N of 2.0% ), while A. strobiliformis displayed a high natural abundance (δ 15 N of 13.5% ). These results are congruent with those of several research teams (Gebauer and Dietrich, 1993, Henn and Chapela, 2001Kohzu et al, 1999;Taylor et al, 2003;Trudell et al, 2004;Zeller et al, 2007) who all observed high 15 N abundance in ectomycorrhizal fungi sporophores. The three Tuber species displayed a high δ 15 N value (9.3 to 10.4% ).…”
Section: Discussionsupporting
confidence: 92%
“…As reported by several authors (Gebauer and Taylor, 1999;Henn and Chapela, 2001;Hobbie et al, 1999Hobbie et al, , 2001Högberg, 1997;Kohzu et al, 1999;Taylor et al, 2003, Trudell et al, 2004Zeller et al, 2007), δ 13 C values differed between sporophores of saprotrophic and ectomycorrhizal fungi. Sporophores of the two saprotrophic fungi from the Châteauvert site showed a 13 C enrichment compared to their substrates.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Stable isotope ratios of N and C differ between ectomycorrhizal and saprotrophic fungi with the general trend showing mycorrhizal fungi enriched in 15 N and depleted in 13 C relative to saprotrophic fungi (Hobbie et al 1999;Högberg et al 1999;Hobbie et al 2001;Hobbie & Horton 2007;Whitridge & Southworth 2005;Hobbie and Högberg 2012). Surveys comparing the isotope ratios of saprotrophic and mycorrhizal fungi at particular sites have focused on epigeous fungi with a low fraction of hypogeous species, i.e., 0/45 (Hobbie et al 2001); 1/135 (Högberg et al 1999;Taylor et al 2003); 1/34 (Hobbie and Agerer 2010) and 0/152 species (Trudell et al 2004). While trophic status might determine the C and N isotopic ratios of both epi-and hypogeous fungi, other factors such as differences in outgassing of volatile compounds, in biomass and nitrogen composition, and in exploration types support the importance of determining isotope ratios for hypogeous fungi (Hobbie and Agerer 2010;D'Auria et al 2013).…”
Section: Introductionmentioning
confidence: 99%